Alternatively spliced myeloid differentiation protein-2 (MD-2s) protein inhibits TLR4-mediated lung inflammation - Tumurkhuu, Gantsetseg (J Immunol, 2015)
We previously identified a novel alternatively spliced isoform of human myeloid differentiation protein-2 (MD-2s) that competitively inhibits binding of MD-2 to TLR4 in vitro. Here we investigated the protective role of MD-2s in LPS-induced acute lung injury by delivering intracheally (i.t.) an adenovirus construct that expressed MD-2s (Ad-MD-2s). After adenovirus-mediated gene transfer, MD-2s was strongly expressed in lung epithelial cells and readily detected in bronchoalveolar lavage fluid (BALF). Compared to Ad-EV control mice, Ad-MD-2s delivery resulted in significantly less LPS-induced inflammation in the lungs, including less protein leakage, cell recruitment, and expression of proinflammatory cytokines and chemokines, such as IL-6, KC, and MIP-2. BALF from Ad-MD-2s mice transferred into lungs of naive mice before i.t. LPS challenge diminished pro-inflammatory cytokine levels. As house dust mite (HDM) sensitization is dependent on TLR4 and HDM Der p 2, a structural homolog of MD-2, we also investigated the effect of MD-2s on house dust mite (HDM)-induced allergic airway inflammation. Ad-MD-2s given before HDM sensitization significantly inhibited subsequent allergic airway inflammation after HDM challenge, including reductions in eosinophils, goblet cell hyperplasia, and IL-5 levels. Our study indicates that the alternatively spliced short isoform of human MD-2 could be a potential therapeutic candidate to treat human diseases induced or exacerbated by TLR4 signaling, such as Gram-negative bacterial endotoxin-induced lung injury and house dust mite-triggered allergic lung inflammation.